Effects of Traditional Chinese Exercises on Cognitive Function in Older Adults With Mild Cognitive Impairment: A Systematic Review and Meta-Analysis - Zhou, Kaixiang; Liu, Meng; Bao, Dapeng; Zhou, Junhong (Frontiers in Human Neuroscience, 2022)
Background: Recently, considerable research has been conducted to study the effects of traditional Chinese exercises (TCEs) on cognitive function in older adults with MCI. We completed a comprehensive systematic review and meta-analysis to assess the efficacy of TCEs on cognitive function in this population. Methods: A search strategy based on the PICOS principle was used to find the literatures in the databases of PubMed, Web of Science, MEDLINE, SPORT-Discus, PsycINFO, Cochrane Central Register of Controlled Trials, Ovid. The quality and risk of bias in the studies were independently assessed by two researchers. Results: Nine trials with 1,290 participants were included. The effect size of TCEs on global cognitive function was small (SMD = 0.29, 95% CI 0.15 to 0.44, p < 0.001) when compared to the active control and was moderate (SMD = 0.58, 95% CI 0.21 to 0.94, p = 0.002) compared to the inactive control; statistically significant effects were also found for short-term memory (SMD = 0.22, 95% CI 0.05 to 0.39, p = 0.013), long-term memory (SMD = 0.53, 95% CI 0.20 to 0.86, p = 0.002), shifting (SMD = -0.39, 95% CI -0.54 to -0.25, p < 0.001), language ability (SMD = 0.32, 95% CI 0.13 to 0.51, p = 0.001), visuospatial perception (SMD = 0.31, 95% CI 0.15 to 0.46, p < 0.001). Conclusions: This meta-analysis provides clinicians with moderate evidence to recommend that TCEs hold potential to enhance both global cognitive function and multiple domains of cognitive function, which, however, needs to be confirmed and further examined in futures studies. The results of this work provide critical knowledge for the design of future studies implementing TCEs as well as its clinical practice. Future RCTs with rigorous designs are needed to help obtain more definitive conclusions on the effects of TCEs on cognitive function in older adults with MCI.